Exploring the Impact of Instagram Use on Adolescents' Global Diversity Values: A Case Study of Toxic Relationship in Narcissistic Personality Disorder (NPD) - Irma Meidiana Kusumaningtyas; Ambiro Puji Asmaroini; Sunarto Sunarto; Singkir Hudijono (STAI Hubbulwathan Duri, 2024)
This study investigates the impact of Instagram use on adolescents' global diversity values, particularly in the context of toxic relationships exacerbated by Narcissistic Personality Disorder (NPD) traits. A quantitative, cross-sectional survey was conducted with 100 respondents from SMKN 1 Ponorogo and Muhammadiyah Ponorogo University. Data were collected using a questionnaire measuring Instagram use, global diversity values, toxic relationship intensity, and narcissistic tendencies. Analysis included validity, reliability, and T-tests using SPSS software. The findings revealed that Instagram use significantly influences adolescents' global diversity values through an